2020
DOI: 10.3982/ecta13918
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Pricing in Village Economies

Abstract: This paper examines the prices of basic staples in rural Mexico. We document that nonlinear pricing in the form of quantity discounts is common, that quantity discounts are sizable for basic staples, and that the well-known conditional cash transfer program Progresa has significantly increased quantity discounts, although the program, as documented in previous studies, has not affected unit prices on average. To account for these patterns, we propose a model of price discrimination that nests those of Maskin a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…We focus our analysis on the untreated households that did not receive cash transfers; we show, via revealed preference over the nonlinear price systems, that these households have tended to benefit from the price changes that occurred during the observation period. This is consistent with the finding in Attanasio and Pastorino (2020) that the change in the wealth distribution induced by Progresa led to larger quantity discounts (which favored the untreated households because they are usually better-off and consumed more).…”
Section: Empirical Applicationssupporting
confidence: 91%
See 2 more Smart Citations
“…We focus our analysis on the untreated households that did not receive cash transfers; we show, via revealed preference over the nonlinear price systems, that these households have tended to benefit from the price changes that occurred during the observation period. This is consistent with the finding in Attanasio and Pastorino (2020) that the change in the wealth distribution induced by Progresa led to larger quantity discounts (which favored the untreated households because they are usually better-off and consumed more).…”
Section: Empirical Applicationssupporting
confidence: 91%
“…First, we use the deterministic augmented utility model to analyze panel data from the Mexican conditional cash transfer program Progresa. Recently, Attanasio and Pastorino (2020) showed that sellers responded to these transfers by altering the nonlinear prices they charge for staples. We focus our analysis on the untreated households that did not receive cash transfers; we show, via revealed preference over the nonlinear price systems, that these households have tended to benefit from the price changes that occurred during the observation period.…”
Section: Empirical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“… See Imbert and Papp (2015),Muralidharan et al (2017),Jayachandran (2006),Akram et al (2017),Cunha et al (2019) andAttanasio and Pastorino (2020).10 Specifically, all NBFC-MFI regulated entities needed to immediately suspend operations and register with the district-level authorities before resuming any disbursements or collections in that district. The ordinance also capped interest rates at 100%, mandated that collections be made in a public place, and prohibited MFIs from lending to members of Self-Help Groups (SHGs)(Cole and Saleman, 2015).…”
mentioning
confidence: 99%
“…Another assumption is that estimated v and p do not depend on quantities, ruling out nonlinear pricing and other non-constant trader marginal costs (see, e.g., Attanasio and Pastorino, 2020). We also assume that the only cost for the trader is the crop purchase cost and that this cost is linear.…”
Section: Discussion Of Assumptions and Model Validationmentioning
confidence: 99%